Negotiating excess treatment costs in a clinical research trial: the good, the bad and the innovative. Issue 1 (December 2016) - Palmer, Rebecca; Harrison, Madeleine; Cross, Elizabeth; Enderby, Pam
Abstract Barriers to recovering the excess treatment costs associated with health research from local organisations in the United Kingdom can increase research costs, delay completion of high- quality studies and risk disenfranchising health trusts and patients from participation. The authors demonstrate how the process for recovering excess treatment costs at a local National Health Service (NHS) trust level in a multicentre study was inconsistent and resulted in excess effort and cost to the research budget. An innovative example of how an organisation acting as a broker between commissioners and researchers facilitated a more timely excess treatment cost agreement is highlighted. Trial registration Current Controlled TrialsISRCTN68798818, registered on 18 February 2014.